2021
DOI: 10.1007/s11739-021-02725-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and evolution of patients with juvenile-onset Behçet’s syndrome over a 25-year period: insights from the AIDA network

Abstract: Behçet’s syndrome (BS) represents an understudied topic in pediatrics: the main aims of our study were to characterize demographic and clinical features of a cohort of BS patients with juvenile-onset managed in three tertiary referral centers in Italy, evaluate their evolution in the long-term, and detect any potential differences with BS patients having an adult-onset. Medical records of 64 juvenile-onset and 332 adult-onset BS followed-up over a 2-year period were retrospectively analyzed and compared. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
(103 reference statements)
1
13
1
Order By: Relevance
“…On the other hand 410 patients with 3 different disease entities distinct from BD were provided from the Eurofever Database as negative controls to test for the validity of the identified diagnostic criteria (12, 14, 46). Similar to adults, the most common presenting sign and often the first at a mean age of 8 to 9 years is recurrent, widespread multiple or single oral ulcers (44, 47, 48), with Sota et al deriving similar data from the AIDA Registry network (49). Genital ulcers are comparatively less frequent than in adults, however they are the second most common presenting sign in children and are seen predominantly in females.…”
Section: Pediatric Behçet's Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand 410 patients with 3 different disease entities distinct from BD were provided from the Eurofever Database as negative controls to test for the validity of the identified diagnostic criteria (12, 14, 46). Similar to adults, the most common presenting sign and often the first at a mean age of 8 to 9 years is recurrent, widespread multiple or single oral ulcers (44, 47, 48), with Sota et al deriving similar data from the AIDA Registry network (49). Genital ulcers are comparatively less frequent than in adults, however they are the second most common presenting sign in children and are seen predominantly in females.…”
Section: Pediatric Behçet's Diseasementioning
confidence: 96%
“…Similar to adults, the most common presenting sign and often the first at a mean age of 8 to 9 years is recurrent, widespread multiple or single oral ulcers ( 44 , 47 , 48 ), with Sota et al deriving similar data from the AIDA Registry network ( 49 ). Genital ulcers are comparatively less frequent than in adults, however they are the second most common presenting sign in children and are seen predominantly in females.…”
Section: Pediatric Behçet's Diseasementioning
confidence: 99%
“…The prevalence of Behçet disease has significant geographic variation with pooled global prevalence of 10.3 per 100,000 inhabitants, but with prevalence as high as 119 per 100,000 in Turkey to 2.1 per 100,000 for Northern Europe (31). Behçet disease can be associated with severe uveitis, with panuveitis being the most commonly observed location for uveitis (42). Occlusive retinal vasculitis is another common manifestation.…”
Section: Association With Systemic Diseasementioning
confidence: 99%
“…Occlusive retinal vasculitis is another common manifestation. A recent study by Sota et al compared 64 juvenile-onset and 332 adult-onset Behçet disease patients, and showed that those with juvenileonset Behçet disease (first manifestation of disease before age 16) have a lower prevalence of uveitis than adult-onset Behcet disease (42). Male patients may have higher risk for severe ocular involvement than female patients (43).…”
Section: Association With Systemic Diseasementioning
confidence: 99%
“…Behçet’s disease (BD) is a chronic systemic inflammatory disorder classically characterized by recurrent aphthous stomatitis, genital ulcers, and uveitis [ 1 ]. Nevertheless, this is a multi-system vasculitis able to involve blood vessels of all types and sizes, and any tissue or organ can be affected [ 2 ]. Worldwide frequency varies by geographical area, with the highest along the ‘Silk Route’ from the East of Asia to the Middle East including the countries around the Mediterranean basin.…”
Section: Introductionmentioning
confidence: 99%